Treatment outcomes of pulpotomy in primary molars utilizing 2.25% sodium hypochlorite gel: a randomized controlled trial - Mawia Karkoutly; Amirah Alnour; Amjad Abu Hasna; Ok Hyung Nam; Saleh Al Kurdi; Nada Bshara (BMC Oral Health)
Abstract Background Sodium hypochlorite (NaOCl) gel can be a potential substitute in daily pediatric dentistry practice. Given its high antimicrobial efficacy, NaOCl gel is expected to induce healing and improve pulpotomy treatment outcomes. This study aimed to perform a histological, clinical, and radiographical evaluation of pulpotomy in human primary molars utilizing 2.25% (NaOCl) gel as a medicament, followed by white mineral trioxide aggregate (WMTA) as a base material. Materials and methods A randomized, second-blinded, split-mouth clinical trial was conducted in cooperative patients aged 8–10 years with 48 carious first primary molars, which were treated by: (I) NaOCl gel group: following hemostasis, teeth were pulpotomized utilizing 2.25% NaOCl gel, and then WMTA paste was applied as a dressing material, and (II) control group: following hemostasis, WMTA paste was applied as a dressing material. Later, each group was sub-divided into three sub-groups (n = 8) according to the time planned for serial extraction: (I) 7 days, (II) 30 days, and (III) 90 days for histological evaluation. In addition, 40 s primary molars in cooperative patients aged 5–10 years indicated for pulpotomy were randomly allocated into two groups for clinical and radiographical evaluation at 3, 6, and 12 months follow-up. Data were analyzed by applying the chi-square test (p < 0.05). Results NaOCl gel improved odontoblastic integrity and dentin bridge formation (p < 0.001) without increasing pulp necrosis or calcifications. The NaOCl gel group showed a 90% clinical and radiographical success rate at 3, 6, and 12 months of follow-up. In the control group, the clinical success rate was 85% after 3, 6, and 12 months, whereas the radiographical success rate was 100% at 3 months and decreased to 85% after 6 and 12 months. Conclusions Utilizing 2.25% NaOCl gel as a medicament in human primary molars pulpotomy improved the treatment outcomes of the WMTA. Trial registration ISRCTN registry, ISRCTN15908457, registered 22 July 2024.